Profil Sensori Kopi Blend dari Beberapa Kultivar Arabika Gayo - Putra, Mardan Syah; Abubakar, Yusya'; Widayat, Heru Prono (Jurnal Teknologi dan Industri Pertanian Indonesia, 2024)
Coffee diversity contributes significantly to the richness and uniqueness of taste, because each coffee type or cultivar carries out its intrinsic quality as a reflection of its genetic characteristic. The aims of this study is to examine the effect of blending of several Gayo Arabica coffee cultivars on the coffee brew sensory profile. This study uses quantitative descriptive analysis (ADK). Experimental design used is one factor ANOVA with 7 combination ratio. Combination of 3 and 2 cultivars were also to be analyzed with different mixing of 3 and 2 cultivars. The samples were then tested for taste including Aroma, Flavor, Aftertaste, Acidity, Body, Balance, and Overall by expert panelists. The data were analyzed using the Mann-Whitney test because the data did not have a normal/nonparametric distribution. The results of the analysis of variance showed that there was no significant difference between the blending treatment and the control treatment on the taste quality scores tested (P0.05). Based on the descriptive, there is a difference in the taste quality score between the blending treatment and the control treatment on the total score of Gayo Arabica coffee taste quality.